Pemanfaatan Gamelan Digital Berbasis Aplikasi Gawai dalam Pembelajaran Karawitan Jawa pada Kelas VIII SMP Negeri 1 Cepu Kabupaten Blora - Gunawan, Gunawan; Muhammad Jazuli; Wandah Wibawanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The research problem in this study is: How is the application of mobile device-based digital gamelan implemented in the learning process of Javanese Gamelan in class VIII students at SMP Negeri 1 Cepu, Blora Regency? The purpose of this study is to describe the implementation of mobile device-based digital gamelan in Javanese Gamelan learning in class VIII at SMP Negeri 1 Cepu, including the stages of planning, implementation, and evaluation. This study uses a qualitative descriptive approach. Data collection techniques include direct observation, in-depth interviews, and documentation. Data analysis is carried out through three main stages: data reduction, data presentation, and conclusion drawing. The results of the tests conducted to evaluate the learning process using mobile device-based digital gamelan show that the observed assessment aspects—namely cohesion, timing accuracy, and pitch accuracy—show positive results. Of the 28 students sampled, 6 students were categorized as